The impact of hospital privatisation on industrial relations and employees: the case of the Hamburg hospitals. (1st October 2008) - Nils Böhlke
Abstract : The privatisation of Hamburg's State Enterprise Hospitals (LBK Hamburg) represents a defining moment in a general trend in the German hospital sector. Carried out in 2005, this privatisation had a far-reaching impact on industrial relations in the hospitals as well as on the working conditions of the employees. These developments cannot only be attributed to the privatisation per se, however; increases in the workloads of hospital workers can also be observed in public clinics. Nevertheless, the deterioration of established collective bargaining procedures and working condition in the privatised clinics have been dramatic, representing an important turning point for hospital employees and their trade union representatives. Drawing on case study research involving interviews with a range of stakeholders, this article describes the privatisation process and its impact on working conditions, employment and industrial relations.